Recommendations for vaccination against shingles - Wyleciał, Zuzanna; Pyla, Eliza; Zamachowska, Wiktoria; Ząber, Julia (Quality in Sport, 2025)
Introduction and purpose: Shingles, or herpes zoster, is a painful condition caused by the reactivation of the varicella-zoster virus, the same virus responsible for chickenpox. Vaccination is the most effective way to prevent shingles and its complications, including postherpetic neuralgia (PHN), a chronic and debilitating nerve pain condition. Vaccination is the most effective way to prevent shingles and its associated complications. This article provides an overview of current recommendations for shingles vaccination, including who should be vaccinated, the available vaccines, and key considerations. Materials and methods: A literature search was conducted by analysing scientific articles published in Google Scholar, PubMed, and UpToDate using keywords included: shingles, vaccination, varicella-zoster virus, infection. We also searched current recommendations of Centers for Disease Control and Prevention. Description of the state of knowledge: Shingles is a common condition, especially in older adults and those with weakened immune systems. While the disease itself can cause significant pain and discomfort, the risk of complications increases with age and other health conditions. Vaccination offers robust protection against shingles and its complications, reducing the overall health burden. Consulting a healthcare provider is advised to determine the best vaccination approach based on individual health conditions. Conclusion: Vaccination against shingles is a critical preventive measure for adults, particularly those aged 50 and older or individuals with weakened immune systems. Shingrix is the recommended vaccine due to its high efficacy and long-lasting protection. Patients should discuss their vaccination plans with healthcare provider to determine the optimal timing and ensure it aligns with their health needs. By staying proactive, individuals can significantly reduce their risk of shingles and enjoy better long-term health.